Non-steady state 2D numerical simulation of gas-liquid phase transition in metal vapour - Kaupuzs, Jevgenijs; Rimshans, Janis (Computer Assisted Methods in Engineering and Science, 2023)
A mathematical model of diffusion of vaporized interacting metal molecules in a fireproof material is considered. The model is based on microscopic kinetic equations describing the process under condition of a strongly non-homogeneous temperature field. A two-dimensional structure is examined, where the inner hot surface acts as the source of metal vapour and the outer surface - as a cooler. Due to interaction between metal molecules, a phase transition (condensation) proceeds near the outer surface. A conservative, monotonous, and absolutely stable difference scheme is developed on the basis of a special exponential substitution for the concentration of molecules. Results of 2D numerical experiments in non-steady state are presented.